Quantum Heisenberg antiferromagnets: a survey of the activity in Firenze - Balucani, Umberto; Capriotti, Luca; Cuccoli, Alessandro; Fubini, Andrea; Roscilde, Tommaso; Tognetti, Valerio; Vaia, Ruggero; Verrucchi, Paola (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2005)
Over the years the research group in Firenze has produced a number of theoretical results concerning the statistical mechanics of quantum antiferromagnetic models, which range from the theory of two-magnon Raman scattering to the characterization of the phase transitions in quantum low-dimensional antiferromagnetic models. Our research activity was steadily aimed to the understandingof experimental observations.